Prognostic impact of alterations in E-cadherin and P-cadherin expression in canine mammary tumors - Gomes, Luciana R.; Ferreira, Enio; Oliveira, Isamara S.; Campos, Cecília B.; Gobbi, Helenice; Cassali, Geovanni D. (Brazilian Journal of Veterinary Pathology, 2021)
Expression of cadherins has been correlated to the development and aggressiveness of epithelial neoplasms, however, in canine mammary tumors, their significance prognostic is uncertain. Due to this fact, the expression of the intracellular adhesion molecules E and P-cadherin and correlation with overall survival were analyzed in 25 canine mammary gland tumors. E-cadherin expression reduction was correlated with histological type, high histological grade, and overall survival rate. P-cadherin staining was higher in malignant tumors, unrelated to other clinicopathological features of aggressiveness. The results of this study suggest a relationship between lower expression of E and P-cadherin and worse prognostic in canine mammary tumors, including shorter overall survival.